Crystal accumulation in a 4.2 Ga lunar impact melt. (1st January 2016) - Norman, M.D.; Taylor, L.A.; Shih, C.-Y.; Nyquist, L.E.
Abstract: The ages of lunar impact basins and the role of fractional crystallization in producing compositional heterogeneity of lunar melt sheets are long-standing problems with significant implications for solar system dynamics and the petrologic evolution of the lunar crust. Here we document the formation of a basin-scale impact on the Moon at 4.20 ± 0.07 Ga based on the 147 Sm– 143 Nd isochron age of a magnesian, noritic anorthosite melt rock from lunar breccia 67955. Major element compositions of plagioclase and mafic silicates in the melt rock imply a substantial component of primary Mg-suite cumulates or related lithologies in the pre-impact crustal stratigraphy. Trace element compositions of the plagioclase, including diagnostic ratios such as Sr/Ba, are also mostly similar to those in plagioclase from Mg-suite cumulates, with a small number of grains trending toward compositions observed in ferroan anorthosites. Mineral-melt distribution coefficients applied to trace element compositions of the 67955 plagioclase and pyroxene predict parental melt compositions that contrast strongly with the bulk rock. Compared to the whole rock, parental melts calculated from the plagioclase are enriched in REE (ΣREELa–Yb = 131–885, average 619 ppm vs. 39.8 ppm) and they have more fractionated REE patterns (La/Ybn = 1.2–9.8, average 4.9 vs. 1.5) with deep negative Eu anomalies (Eu/Eu ∗ = 0.09–0.40 vs. 1.36). Trace element data for the pyroxenes also imply incompatible-element enriched parental melts. Subsolidus equilibration between the plagioclase and the pyroxene apparently rotated the REE patterns, but the conclusion that the parental melt was highly enriched in REE relative to the whole rock appears robust. Quantitative modeling shows that fractional crystallization of the 67955 whole rock composition cannot reproduce the range of Ba, Sr, Ti, and La concentrations measured in the 67955 plagioclase. Rather, the models require an initial melt composition that was strongly enriched in these elements, and they suggest that fractional crystallization became less efficient as crystallization proceeded. The contrast between the inferred parental melt composition and the bulk rock implies formation of the 67955 noritic anorthosite as a crystal cumulate, and that the cogenetic residual melt was strongly enriched in incompatible elements. If so, this would be the first documented example of fractional crystallization in a lunar impact melt sheet. The petrological and geochemical characteristics of the 67955 noritic anorthosite suggest that it formed by an impact in the Procellarum-KREEP Terrane, and was transported to the Apollo 16 site as Imbrium ejecta. Inheritance of ejecta related to this pre-Imbrium basin may contribute to the common occurrence of ∼4.2 Ga 40 Ar– 39 Ar plateau ages in breccia clasts and regolith fragments from the rim of North Ray crater. In that case, those data may provide no constraints on the age of the Nectaris basin, despite its proximity to the Apollo 16 site.